Image Recognition, Static Hand Gesture Recognition Software - Kapoun, Jan (Jihočeská univerzita, 2011)
This thesis deals with recognition of static hand gestures in a real-time video feed. It is an accompanying paper to the application that I created. Within the framework of this thesis, you will find necessary algorithms for background segmentation and image recognition that were implemented in the application. This thesis also describes problems that I came across when writing the software and also some dead-ends I found when trying to choose the best algorithms. The application source code along with images and a video presentation can be downloaded here: http://jankapoun.own.cz/soft_AI.php
Image Recognition
Keywords: image recognition; hand gestures; artificial intelligence; Hu moments; background subtraction; contour finding; image recognition; hand gestures; artificial intelligence; Hu moments; background subtraction; contour finding